חֶסֶד and Ikharari : the book of Ruth from a Lomwe perspective - Alfredo, Justino Manuel (Stellenbosch : University of Stellenbosch, 2010)
Thesis (DTh (Old and New Testament))--University of Stellenbosch, 2010.